2017
DOI: 10.1371/journal.pone.0174158
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early versus late initiation of renal replacement therapy in patients with acute kidney injury: A meta-analysis with trial sequential analysis of randomized controlled trials

Abstract: BackgroundThe optimal timing for initiating renal replacement therapy (RRT) in patients with acute kidney injury (AKI) remains controversial.MethodsWe conducted a meta-analysis with trial sequential analysis (TSA) of randomized controlled trials (RCTs) using PUBMED, Cochrane Library databases, and Web of Science (from January 1, 1985, to August 21, 2016). Adult patients with AKI who received RRT with different timing were included. The primary outcome was mortality. The secondary outcomes were intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…Our present review did not demonstrate a statistically significant survival benefit of early RRT initiation, which is in line with the findings of most previous reviews [5][6][7][8][9][10]. Several studies that revealed positive [13] or negative [14,29,30] effects of early RRT initiation were not included in our meta-analysis.…”
Section: Present Studysupporting
confidence: 91%
See 2 more Smart Citations
“…Our present review did not demonstrate a statistically significant survival benefit of early RRT initiation, which is in line with the findings of most previous reviews [5][6][7][8][9][10]. Several studies that revealed positive [13] or negative [14,29,30] effects of early RRT initiation were not included in our meta-analysis.…”
Section: Present Studysupporting
confidence: 91%
“…Several recent meta-analyses examined the effect of early RRT initiation on patient survival and related outcomes [5][6][7][8][9][10][11]. All but one meta-analysis [11] reported that the early initiation of RRT did not provide a survival advantage (Additional file 1: Table S7).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous studies investigating the relationship between mortality and the timing of RRT initiation, it remained controversial whether early initiation of RRT improved outcomes. In 2016, two RCTs and in 2017 nine systematic reviews and meta‐analyses evaluated the optimal timing of RRT initiation for AKI. A multicenter RCT study, the Artificial Kidney Initiation in Kidney Injury (AKIKI) study, conducted in France, showed that there were no significant differences in mortality between early and late initiation of RRT .…”
Section: Rrt For Akimentioning
confidence: 99%
“…Early initiation of RRT (defined as KDIGO stage 3 AKI) in the AKIKI study corresponded to the delayed arm in the ELAIN study. Turning to the conclusions of nine meta-analyses,[90][91][92][93][94][95][96][97][98] the AKI patients in the RCTs who underwent early initiation of RRT did not show a lower mortality rate than those with late RRT [90][91][92][93][94]96,98.…”
mentioning
confidence: 99%